Did floating rate notes stopped floating? An investigation on legal impacts of negative interest rates on bond agreements and their trade - Klaus, Jürgen (Riga Graduate School of Law, 2018)
Most securities pay a coupon as a form of interest from the borrower to the lender. While interest rates in the Euro Area are at historical low levels, as a common market practice, fixed income bonds can yield negatively and trade without material impacts. However, negative rates impact securities with floating rate coupons and create legal and operational uncertainty whether their coupons can turn negative and if this implies the borrower’s right to debit the bondholder. The thesis analyses if the applicable bond documentations are clear on the treatment of negative interest rates. Further, it interprets if an issuer could legally enforce to claim a payment from the investor under English law governed bond agreements.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Financial law; Bonds